A Case of Neuropathic Lower Urinary Tract Dysfunction Due to Spina Bifida Occulta Discovered at the Age of 19 Years and Successfully Treated with Multidisciplinary Therapy - Muranaka, Ippei (Hinyokika kiyo. Acta urologica Japonica, 2024)
A 19-year-old man had been aware of dysuria and urinary incontinence since childhood but did not seek medical attention. He was diagnosed with acute pyelonephritis due to lower urinary tract dysfunction associated with spina bifida occulta and tethered cord syndrome (TCS) due to spinal cord lipoma. After placement of a urethral catheter and antibacterial chemotherapy, the patient was cured of acute pyelonephritis. He was treated with solifenacin and started clean self-intermittent catheterization (CIC). Shortly after the start of CIC, the acute pyelonephritis flared up again, and he was managed with a reinserted urethral catheter until an untethering operation. Preoperative video urodynamics showed that the bladder morphology was Ogawa classification grade III with vesicoureteral reflux (VUR) at 92 ml infusion. With the combination of an untethering operation and additional mirabegron, the functional bladder capacity was increased to 353 ml and VUR improved, allowing for safe urinary management of the CIC. TCS can be diagnosed at any age and requires appropriate urinary management and therapeutic intervention as early as possible after diagnosis